The Legal Status of Evidence obtained through Human Rights Violations in Uganda - Nanima, Robert D. (Academy of Science of South Africa, 2017)
The Constitution of the Republic of Uganda, 1995 (Constitution of 1995) is silent on the issue of dealing with evidence obtained through human rights violations. This silence dates to the Constitutions 1962, 1966 and 1967.  It is only the Prohibition and Prevention of Torture Act of 2012 that renders evidence obtained through torture inadmissible.  This means that evidence obtained through human rights violations, other than torture is not covered by any other legislation in Uganda. The position is different in other common law jurisdictions such as South Africa, Kenya and Zimbabwe, which have constitutional provisions on how to deal with evidence obtained through human rights violations. Decisions handed down by the Courts are inconsistent in dealing with this kind of evidence. This comparative study coupled with Uganda’s international human rights obligations delves into this lacuna in the law and gives proposals for reform.